MEMBANGUN NILAI KARAKTER RELIGIUS MELALUI AKTIVITAS KEAGAMAAN DI MTs AL YAKIN PUNGPUNGAN - sahri sahri (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
Schools have an important role in shaping the personality and behavior of children. Schools that want to succeed in shaping religious character must be able to implement a variety of religious activities that support this goal. Religious activities carried out by MTs Al Yakin that they must be carried out continuously. The purpose of this study is to describe the activities of MTs al-Yakin in developing religious character values ​​for students through religious activities. This type of research is qualitative. In collecting data using interview techniques, observation and documentation. Based on the data obtained in this study, there are several religious activities that are able to support and shape religious character values, namely the existence of reciting activities every morning, reading Asmaul Husna, dhuha prayer, dhuhur prayer, Friday charity, ramadan cottage, extracurricular reading write the Qur'an, the commemoration of Isra' and Mi'raj as well as the commemoration of the birthday of the Prophet Muhammad